2016
DOI: 10.2214/ajr.16.16161
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training May Improve Resident Skill in Ultrasound-Guided Biopsy

Abstract: Simulation-based training improves overall procedure time, number of skin punctures and needle adjustments, and subjective performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Of the 14 studies in the review, only 5 included a control group, and only 2 of those were randomized. Since this publication, multiple controlled randomized trials have reported the potential benefits of ultrasound simulators . In addition, ultrasound simulators allow trainees to practice multiple times the same ultrasound modality without the need of supervisors or models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 14 studies in the review, only 5 included a control group, and only 2 of those were randomized. Since this publication, multiple controlled randomized trials have reported the potential benefits of ultrasound simulators . In addition, ultrasound simulators allow trainees to practice multiple times the same ultrasound modality without the need of supervisors or models.…”
Section: Discussionmentioning
confidence: 99%
“…Since this publication, multiple controlled randomized trials have reported the potential benefits of ultrasound simulators. 3,4,[6][7][8][9][10][11][12][13] In addition, ultrasound simulators allow trainees to practice multiple times the same ultrasound modality without the need of supervisors or models. This can improve scanning proficiency, as it has been shown that the number of successful scans increases with repeated scanning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have aimed to create technical improvements in US training, including the acquisition of high-quality images or the detection of target lesions using various training methods, such as lectures, hands-on sessions, and apprenticeships with an experienced radiologist. 8 9 10 11 12 13 However, no studies have addressed the problem of how to improve the evaluation of static US images, especially when the examiner and the interpreter are not the same person.…”
Section: Introductionmentioning
confidence: 99%